Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy

Microbial selenium nanoparticles (SeNPs) and their application as a sensitive hydrogen peroxide biosensor - Prasad, Kumar Suranjit; Vaghasiya, Jayraj V.; Soni, Saurabh S.; Patel, Jitesh; Patel, Rinkesh; Kumari, Madhu; Jasmani, Falguni; Selvaraj, Kaliaperumal (Applied Biochemistry and Biotechnology, 2015)
The cell-free extract, a crude enzyme (cytosolic and membrane fraction) obtained from an environmental isolate, Bacillus pumilus sp. BAB-3706 worked as excellent in reducing as well as stabilizing agent and facilitated the formation of stable colloidal selenium nanoparticles (SeNPs). Resulting nanoparticles were characterized using UV-vis spectrophotometer, TEM, EDAX, FT-IR and XRD, respectively. A working electrode was modified by coating the surface of indium tin oxide (ITO) with colloidal SeNPs. Successive additions of H2O2 (100 to 600 mu M) in conventional three electrodes system, cyclic voltammeter with potential scan rate 25.0 mV/s, in 0.1 M phosphate buffer solution (PBS) yielded increase in current. A perpetual amperometric response at fixed potential (-1.0 V) and at selected time interval of 100 s showed different magnitude of current at every addition of H2O2. The linear range of detection of H2O2 was from 5 to 600 mM (R (2) = 0.9965), while the calculated limit of detection was found to be 3.00 mu M. The current study suggested that microbial SeNPs can be used for fabrication of low cost, sensitive H2O2 biosensor.
Keywords: Biosensor; EDAX; Hydrogen peroxide; Selenium nanoparticles; TEM; UV-vis spectroscopy

Synergistic electronic effects in AuCo nanoparticles stabilized in a triazine-based covalent organic framework: a catalyst for methyl orange and methylene blue reduction - Devulapalli, Venkata Swaroopa Datta; Kushwaha, Rinku; Ovalle, Edwin; Singh, Himan Dev; Shekhar, Pragalbh; Chakraborty, Debanjan; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan; Borguet, Eric (ACS Applied Nano Materials, 2022)
Developing stable active catalysts for reducing water-soluble pollutants is a desirable target. In this pursuit, we have functionalized covalent organic frameworks (COFs) with gold (Au) and cobalt (Co) nanoparticles via a one-step aqueous synthesis process, and their catalytic activity in reducing methyl orange and methylene blue is examined. Operando absorbance measurements of methyl orange (anionic dye) reduction revealed AuCoCOF (1.3 Au/1.0 Co) to have superior kinetics over many other catalysts, which typically require additional external stimuli (e.g., photons) and higher catalyst loadings. After confirming the homogeneous dispersion of the nanoparticles on the COF support using three-dimensional (3D) tomography and material stability through powder X-ray diffraction (PXRD), infrared (IR), and thermal studies, we investigated their redox activity. Cyclic voltammetry (CV) confirmed the involvement of both metals in the redox process, while spectroelectrochemical measurements show that their activity and kinetics remain unaltered by an applied potential. Solid-state UV measurements reveal that the neat COF is a semiconductor with a large band gap (2.8 eV), which is substantially lowered when loaded with cobalt nanoparticles (2.2 eV for CoCOF). The electronic synergy between Au and Co nanoparticles further reduces the band gap of AuCoCOF (1.9 eV). Thus, there is a definite advantage in doping non-noble metal nanoparticles into a noble metal lattice and nanoconfining them into a porous COF support. Our study highlights the significance of bimetallic COF-supported nanocatalysts, wherein one can engage each component toward targeted applications that demand redox activity with favorable kinetics.
Keywords: AuCoCOF; band gaps; Covalent organic framework; methyl orange reduction; Nanoparticles; UV-vis spectroscopy